Randomized control trials demonstrate that nutrition-sensitive social protection interventions increase the use of multiple-micronutrient powders and iron supplements in rural pre-school Bangladeshi children - Hoddinott, John F.; Ahmed, Akhter; Roy, Shalini (Cambridge University Press, 2018)
Objective To examine the impact of a nutrition-sensitive social protection intervention on mothers’ knowledge of Fe deficiency, awareness of multiple-micronutrient powders (MMP) and the consumption of MMP and other Fe supplements by their children aged 6–59 months. Design Two randomized controlled trials with treatment arms including cash transfers, food transfers, cash and food transfers, cash and nutrition behaviour change communication (BCC), and food and nutrition BCC were implemented over two years. Both included a control group that received no transfer or BCC. Transfer recipients were mothers living in poor households with at least one child aged less than 2 years at baseline. Probit models were used to analyse endline data. Setting Rural areas in north-west and south Bangladesh. Subjects Mothers (n 4840) and children 6–59 months (n 4840). Results A transfer accompanied by nutrition BCC increased the share of mothers with knowledge of Fe deficiency (11·9 and 9·2 percentage points for North and South, respectively, P≤0·01), maternal awareness of MMP (29·0 and 22·2 percentage points, P≤0·01), the likelihood that their children 6–59 months had ever consumed MMP (32 and 11·9 percentage points, P≤0·01), consumed MMP in the preceding week (16·9 and 3·9 percentage points, P≤0·01) and consumed either MMP or an Fe supplement in the preceding week (22·3 and 7·1 percentage points, P≤0·01). Improvements were statistically significant relative to groups that received a transfer only. Conclusions Nutrition-sensitive social protection (transfers with BCC added) may be a promising way to advance progress on micronutrient deficiencies.